Setting the standard: a bibliometric analysis of leadership styles and their effect on job performance / Rosliza Md Zani ... [et al.] - Md Zani, Rosliza; Ali, Syukriah; Anuar, Azyyati; Abdullah, Fatihah Norazami; Ali Akbar, Yong Azrina (Universiti Teknologi MARA, Perlis, 2025)
Effective leadership plays a crucial role in boosting employee engagement and productivity, with numerous studies linking leadership styles to job performance. However, most of this research focuses on developed economies, leaving a gap in understanding leadership's impact in emerging markets, where unique cultural and economic factors may necessitate different approaches. This study addresses this gap by conducting a bibliometric analysis of global research on leadership styles, with an emphasis on emerging markets. Using data from Scopus and tools like VOSviewer and Harzing’s Publish or Perish, the study examines trends in publication, authorship, geographic distribution, and citation metrics. Findings show that transformational and authentic leadership styles are widely researched, primarily in developed regions, while emerging markets remain underrepresented. This study highlights the need for more targeted research to address the specific challenges of these regions. Theoretical implications suggest developing leadership models suited to emerging markets, while practical implications encourage organizations to adapt leadership practices that align with local socioeconomic realities. By filling a critical gap in the literature, this research lays the groundwork for future studies on leadership effectiveness across diverse, less-studied contexts.